Efficacy, safety and feasibility of fosaprepitant for the prevention of chemotherapy-induced nausea and vomiting in pediatric patients receiving moderately and highly emetogenic chemotherapy – results of a non-interventional observation study - Semjon Willier; Karin Melanie Cabanillas Stanchi; Martina von Have; Vera Binder; Franziska Blaeschke; Judith Feucht; Tobias Feuchtinger; Michaela Döring (BMC Cancer, 2019)
Abstract Background Chemotherapy-induced nausea and vomiting (CINV) belong among the most burdensome side effects in hemato-oncology. Mostly, a combination of ondansetron and dexamethasone is used as antiemetic prophylaxis in pediatric patients undergoing emetogenic chemotherapy. However, dexamethasone is prohibited in different pediatric chemotherapy protocols. Currently, data on the use of ondansetron with the new antiemetic agent fosaprepitant without dexamethasone is not available for pediatric patients. Methods In this non-interventional observation study, 79 pediatric patients with a median age of 8.0 years (range 0.5–17.9 years) who received a CINV prophylaxis regimen with either fosaprepitant (4 mg/kg; maximum 150 mg) and ondansetron (as 24-h continuous infusion) (n = 40; fosaprepitant group/FG) or ondansetron only (n = 39; control group/CG) during moderately or highly emetogenic chemotherapy were analyzed. The groups were analyzed and compared for frequency of vomiting, administered doses of on-demand antiemetic dimenhydrinate and adverse events during the acute (0-24 h after chemotherapy administration) and delayed (> 24 h–120 h) CINV phases. Results A total of 112 and 116 chemotherapy blocks were analyzed in the fosaprepitant and the control group, respectively. The emetogenic potential of the administered chemotherapy did not significantly differ (p = 0.8812) between the two cohorts. In the acute CINV phase, the percentage of patients experiencing vomiting (n = 26 patients) and the vomiting events were significantly higher (p = 0.0005 and p < 0.0001, respectively) in the CG (n = 26 patients (66.7%); 88 events) compared with the FG (n = 10 patients (25.0%); 37 events). In the delayed CINV phase, the percentage of patients experiencing vomiting and the vomiting events were also significantly higher (p = 0.0017 and p < 0.0001, respectively) in the CG (n = 31 patients (79.5%); 164 events) compared with the FG (n = 17 patients (42.5%); 103 events). Additionally, significantly more dimenhydrinate doses were administered in the CG compared with the FG patients (n = 322/n = 198; p < 0.0001). The occurrence of adverse events did not significantly differ between the two groups (p > 0.05). Conclusion Fosaprepitant (4.0 mg/kg) in addition to ondansetron, without application of dexamethasone, was well tolerated, safe, effective and superior to ondansetron only as CINV prophylaxis in pediatric patients during moderately and highly emetogenic chemotherapy.